Use of intravascular ultrasound and long-term cardiac death or myocardial infarction in patients receiving current generation drug-eluting stents - Sang Yoon Lee; Ki Hong Choi; Young Bin Song; Taek Kyu Park; Joo Myung Lee; Jeong Hoon Yang; Jin-Ho Choi; Seung-Hyuk Choi; Hyeon-Cheol Gwon; Joo-Yong Hahn (Scientific Reports, 2022)
Abstract Long-term follow-up data on differential effects of intravascular ultrasound (IVUS) according to lesion complexity are limited in patients undergoing percutaneous coronary intervention (PCI). The current study compared long-term clinical outcomes between IVUS-guided and angiography-guided PCI in patients with second-generation drug-eluting stents (DES). Between February 2008 and December 2015, 5488 patients undergoing PCI with second-generation DES were recruited from an institutional registry of Samsung Medical Center. The primary outcome was a composite of cardiac death or myocardial infarction (MI) during 46 months of median follow-up (interquartile range: 32–102 months). IVUS-guided PCI was performed in 979 patients (17.8%). IVUS-guided PCI was associated with a significantly lower risk of cardiac death or MI compared with angiography-guided PCI (5.7% vs. 12.9%, hazard ratio 0.408, 95% confidence interval 0.284–0.587, p < 0.001). Results were consistent after propensity score matching analysis with 801 matched pairs. In subgroup analysis, there was no significant interaction between lesion complexity (defined by complex procedures, Pinteraction = 0.819, ACC/AHA lesion classification, Pinteraction = 0.401 or SYNTAX score, Pinteraction = 0.149) and use of IVUS for risk of cardiac death or MI. IVUS-guided second-generation DES implantation was associated with a significantly lower long-term risk of cardiac death or MI compared with angiography guidance, regardless of lesion complexity.